Evaluating The Philippine TVET Competency Assessment and Certification System Using SERVQUAL Model - Francisco, John Mark; Jasmin, Neri (Journal of Technical Education and Training, 2023)
The TVET program has been successful in providing highly skilled individuals to meet the demands of the labor market. However, it is important to evaluate the delivery of the program to ensure that it continues to meet these demands. This study focused on analyzing the delivery of the TVET competency assessment and certification system in Davao de Oro, Philippines. The study utilized a descriptive survey method and adopted the (Service Quality) SERVQUAL model to assess service quality. The results revealed that there is a gender gap distribution among male and female clients who availed of the process of competency assessment and certification system. The study also found that empathy obtained a negative gap score (-0.03) in the process. This negative score implies that empathy is as important as other dimensions of service quality. However, other dimensions of service quality have met the expectations of clients and obtained a positive score. Overall, respondents have perceived the implementation of the technical vocational education and training TVET competency assessment and certification system to be satisfactory. To improve the service quality, it is necessary to provide appropriate information about processing time and documentary requirements to all clients and equip personnel in handling clients proactively. Relationship-based management should also be improved to promote holistic technical vocational education and training (TVET) service quality, particularly in competency assessment and certification systems.